Biomarkers in scleroderma: Current status - Latika Gupta; Sanat Phatak; Sukesh Edavalath (Indian Journal of Rheumatology)
Scleroderma is an autoimmune disease characterized by indolent obliterative vasculopathy and widespread fibrosis. The two main morphological manifestations of the disease overlap and may make it difficult to separate activity from damage. Many patients, especially those with the limited subset of the disease, have an indolent course without clear-cut inflammatory manifestations. There is a felt need for validated biomarkers, which can differentiate activity from damage, and yet be sensitive to change with therapy. Multiplex arrays of biomarkers have ushered an era of targeted or personalized medicine based on phenotypic characteristics in an individual.